138. Toward adaptive radiotherapy: Morphological and setup variability in head and neck TomoTherapy treatments. (December 2018) - Redapi, L.; Gagliano, A.; Marrazzo, L.; Calusi, S.; Talamonti, C.; Arilli, C.; Bonomo, P.; Pallotta, S.
Abstract: Purpose: In head and neck (H&N) radiotherapy, an essential requirement is the reproducibility of the relative position of head and neck during the whole treatment. Moreover, adaptive radiotherapy for H&N cancer would benefit from indicators capable of easily identifying morphological alterations. Aim of this study was to test whether the immobilization device guarantees a reproducible head and neck position and to identify, on set-up verification images, some indicators capable of describing morphological alterations. Methods and materials: A retrospective analysis on 15 patients immobilized using s-shaped head-neck-shoulders masks and treated with TomoTherapy (50–70 Gy/25-33fr) was conducted. For each treatment session two MVCT-CT registrations were performed alternatively optimizing matching on the head or the neck. For each patient mean differences between the two registrations parameters ( Δ x, Δ y, Δ z, Δ pitch, Δ roll, Δ yaw) over all treatment sessions were evaluated. Morphological alterations were studied (once a week for the whole treatment duration) by measuring on MVCT images the skin-to-skin distance at 3 different antero-posterior levels: at the center of parotid glands (line1) and 2 cm (line 2) and 4 cm (line 3) anteriorly. Mean percentage variations respect to the first week were evaluated for all patients. A Student's t-test was carried out (p < 0, 01). Results: Mean differences between head and neck registration parameters are reported inTable 1 . Except for two patients, mean differences were smaller than 1.7 mm and 1.2°. Mean percentage variations of lines' length are reported in Fig. 1. For all, a decreasing trend was observed. Variations are statistically significant starting from the 4 th week for lines 1 and 2, and only from the 6 th week for line 3. Conclusion: The immobilization device enables adequate H&N set-up during the whole treatment for almost all patients. Lines 1 and 2 drawn on MVCT images seem to be suitable for describing morphological alterations that might deserve re-planning.